A preliminary survey of Buddhist higher education in Asia: developing typologies and comparing secularities. Issue 4 (1st October 2020) - Borchert, Thomas
ABSTRACT: Over the course of the last century, a number of Buddhist institutions of higher learning have been established across Asia. These institutions play an important role in many Asian sanghas, but they have received little scholarly attention. This article maps out some of the diverse aspects of these universities, and sketches out different types of institutions of Buddhist higher education. It argues that while Buddhists have long had advanced educational practices, these institutions are different in that they are founded in the context of nation-building and modernizing efforts. As a result they are entangled with projects that might be thought about as both religious and secular.